Association between olfactory identification and parkinsonism in patients with non‐affective psychosis. Issue 5 (18th September 2014) - Meijer, Julia H.; van Harten, Peter; Meijer, Carin J.; Koeter, Maarten W.; Bruggeman, Richard; Cahn, Wiepke; Kahn, René S.; de Haan, L.; ,
Abstract: Aim: Olfactory identification deficits (OIDs) are seen in schizophrenia patients and individuals at increased risk for psychosis but its pathophysiology remains unclear. Although dopaminergic imbalance is known to lie at the core of schizophrenia symptomatology, its role in the development of OIDs has not been elucidated yet. This study investigated the association between OIDs and symptoms of parkinsonism as a derivative of dopaminergic functioning. Methods: In 320 patients diagnosed with non‐affective psychosis, olfactory identification performance was assessed by means of the Sniffin' Sticks task. Level of parkinsonian symptoms was assessed by means of the Unified Parkinson's Disease Rating Scale (UPDRS‐III). By means of multiple linear regression with bootstrapping, the association between UPDRS and Sniffin' Sticks score was investigated while correcting for potential confounders. A Bonferroni corrected P ‐value of 0.007 was used. Results: Higher UPDRS scores significantly predicted worse olfactory identification in patients with non‐affective psychosis with an unadjusted b = −0.07 (95% CI −0.10 to −0.04) and an adjusted b = −0.04 (95% CI −0.07 to −0.01). Conclusion: Results provide preliminary evidence that the same vulnerability may underlie the development of parkinsonism and OIDs in patients with non‐affective psychosis. Further investigation should evaluate the clinical value of OIDs as a marker of dopaminergic vulnerability that may predict psychosis.